AUDIT COMMITTEE AND FINANCIALLY DISTRESSED FIRMS IN MALAYSIA - I.K Norziaton; S. Hafizah (International Journal of Accounting, Finance and Business, 2019)
The purpose of this study is to investigate the influence of audit committee characteristics on the performance of financially distressed firms (PN17) prior to their suspension by the Bursa Malaysia. Financial distress within large firms is a sign of weak corporate governance practices, of which the audit committee is one of the key elements. Thus, five determinants of audit committee characteristics have been identified which are expertise, size, independence, diligence and multiple directorships. The sample comprises 14 firms which were suspended by the Bursa Malaysia under PN17 in December 2017. A total of 126 published annual reports were collected starting from the financial year end 2009 until 2017. Data was collected from the firms’ annual reports and DataStream. Most prior research has identified audit committee expertise as one of the factors which influence the financial performance of firms. Most of those studies were conducted based on comparisons of audit committee characteristics between financially distressed firms and successful firms. Therefore, this study is vital as it provides additional knowledge to identify the audit committee characteristics that influence financially distressed firms. Five hypotheses have been tested based on audit committee characteristics. Four out of five of these hypotheses are supported, namely audit committee expertise, audit committee independence, audit committee diligence and audit committee multiple directorships. This shows that the audit committee is one of the key players in the corporate governance mosaic, which has an influence on financially distressed firms.